Adrenal hyperplasias in childhood: An update - Pitsava, Georgia; Stratakis, Constantine A. (Frontiers in Endocrinology, 2022)
Pediatric adrenocortical hyperplasias are rare and can present with Cushing syndrome (CS). CS is caused by either exogenous or endogenous hypercortisolemia. Endogenous CS can be adrenocorticotropin (ACTH)-dependent -due to a pituitary tumor (Cushing disease) or due to an ectopic source- or ACTH-independent. ACTH-independent CS accounts for almost half of the younger childhood CS cases. Adrenocortical causes of CS include, among others, bilateral adrenocortical hyperplasias; of them, isolated micronodular adrenal disease and its variant, primary pigmented adrenocortical disease may present in children. Most cases are due to defects in the cyclic AMP/protein kinase A (cAMP /PKA) pathway. Another cause of adrenal hyperplasia in childhood is congenital adrenal hyperplasia, a group of autosomal recessive disorders that affect the synthesis of the steroidogenic enzymes in the adrenal cortex. Clinical presentation varies and depends on the extent of the underlying enzymatic defect. The most common form is due to 21-hydroxylase deficiency; it accounts for more than 90% of the cases. In this article, we discuss the genetic etiology of adrenal hyperplasias in childhood.